![1)(\sqrt{x+2\sqrt{x-1} }-\sqrt{x-2\sqrt{x-1} })^{2} =3^{2}\\\\x+2\sqrt{x-1}-2\sqrt{(x+2\sqrt{x-1})(x-2\sqrt{x-1}})+x-2\sqrt{x-1}=9\\\\2x-2\sqrt{x^{2}-4(x-1) }=9\\\\2\sqrt{x^{2}-4x+4 } =2x-9\\\\\sqrt{(x-2)^{2} }=x-4,5\\\\|x-2|=x-4,5\\\\1)\left \{ {x-2=x-4,5} \atop {x-4,5\geq0 }} \right.\\\\\left \{ {{0*x=-2,5} \atop {x\geq4,5 }} \right. 1)(\sqrt{x+2\sqrt{x-1} }-\sqrt{x-2\sqrt{x-1} })^{2} =3^{2}\\\\x+2\sqrt{x-1}-2\sqrt{(x+2\sqrt{x-1})(x-2\sqrt{x-1}})+x-2\sqrt{x-1}=9\\\\2x-2\sqrt{x^{2}-4(x-1) }=9\\\\2\sqrt{x^{2}-4x+4 } =2x-9\\\\\sqrt{(x-2)^{2} }=x-4,5\\\\|x-2|=x-4,5\\\\1)\left \{ {x-2=x-4,5} \atop {x-4,5\geq0 }} \right.\\\\\left \{ {{0*x=-2,5} \atop {x\geq4,5 }} \right.](https://tex.z-dn.net/?f=1%29%28%5Csqrt%7Bx%2B2%5Csqrt%7Bx-1%7D%20%7D-%5Csqrt%7Bx-2%5Csqrt%7Bx-1%7D%20%7D%29%5E%7B2%7D%20%3D3%5E%7B2%7D%5C%5C%5C%5Cx%2B2%5Csqrt%7Bx-1%7D-2%5Csqrt%7B%28x%2B2%5Csqrt%7Bx-1%7D%29%28x-2%5Csqrt%7Bx-1%7D%7D%29%2Bx-2%5Csqrt%7Bx-1%7D%3D9%5C%5C%5C%5C2x-2%5Csqrt%7Bx%5E%7B2%7D-4%28x-1%29%20%7D%3D9%5C%5C%5C%5C2%5Csqrt%7Bx%5E%7B2%7D-4x%2B4%20%7D%20%3D2x-9%5C%5C%5C%5C%5Csqrt%7B%28x-2%29%5E%7B2%7D%20%7D%3Dx-4%2C5%5C%5C%5C%5C%7Cx-2%7C%3Dx-4%2C5%5C%5C%5C%5C1%29%5Cleft%20%5C%7B%20%7Bx-2%3Dx-4%2C5%7D%20%5Catop%20%7Bx-4%2C5%5Cgeq0%20%7D%7D%20%5Cright.%5C%5C%5C%5C%5Cleft%20%5C%7B%20%7B%7B0%2Ax%3D-2%2C5%7D%20%5Catop%20%7Bx%5Cgeq4%2C5%20%7D%7D%20%5Cright.)
Решений нет
![2)\left \{ {{x-2=4,5-x} \atop {x-4,5\geq0 }} \right.\\\\\left \{ {{y=2} \atop {x=2}} \right. \left \{ {{x+x=6,5} \atop {x\geq4,5 }} \right. \\\\\left \{ {{2x=6,5} \atop {x\geq4,5 }} \right. \\\\\left \{ {{x=3,25} \atop {x\geq4,5 }} \right. 2)\left \{ {{x-2=4,5-x} \atop {x-4,5\geq0 }} \right.\\\\\left \{ {{y=2} \atop {x=2}} \right. \left \{ {{x+x=6,5} \atop {x\geq4,5 }} \right. \\\\\left \{ {{2x=6,5} \atop {x\geq4,5 }} \right. \\\\\left \{ {{x=3,25} \atop {x\geq4,5 }} \right.](https://tex.z-dn.net/?f=2%29%5Cleft%20%5C%7B%20%7B%7Bx-2%3D4%2C5-x%7D%20%5Catop%20%7Bx-4%2C5%5Cgeq0%20%7D%7D%20%5Cright.%5C%5C%5C%5C%5Cleft%20%5C%7B%20%7B%7By%3D2%7D%20%5Catop%20%7Bx%3D2%7D%7D%20%5Cright.%20%5Cleft%20%5C%7B%20%7B%7Bx%2Bx%3D6%2C5%7D%20%5Catop%20%7Bx%5Cgeq4%2C5%20%7D%7D%20%5Cright.%20%5C%5C%5C%5C%5Cleft%20%5C%7B%20%7B%7B2x%3D6%2C5%7D%20%5Catop%20%7Bx%5Cgeq4%2C5%20%7D%7D%20%5Cright.%20%5C%5C%5C%5C%5Cleft%20%5C%7B%20%7B%7Bx%3D3%2C25%7D%20%5Catop%20%7Bx%5Cgeq4%2C5%20%7D%7D%20%5Cright.)
Решений нет
Ответ : решений нет
0 \\\\4*(\frac{4}{9})^{x}-13*(\frac{6}{9})^{x}+9*(\frac{9}{9})^{x}=0\\\\4*(\frac{2}{3})^{2x} -13*(\frac{2}{3})^{2}+9=0\\\\(\frac{2}{3})^{x}=m,m>0" alt="4^{x+1}-13*6^{x}+9^{x+1}=0\\\\4*4^{x}-13*6^{x}+9*9^{x}=0|:9^{x}>0 \\\\4*(\frac{4}{9})^{x}-13*(\frac{6}{9})^{x}+9*(\frac{9}{9})^{x}=0\\\\4*(\frac{2}{3})^{2x} -13*(\frac{2}{3})^{2}+9=0\\\\(\frac{2}{3})^{x}=m,m>0" align="absmiddle" class="latex-formula">
![4m^{2}-13m+9=0\\\\D=(-13)^{2}-4*4*9=169-144=25=5^{2}\\\\m_{1}=\frac{13+5}{8}=\frac{9}{4}\\\\m_{2}=\frac{13-5}{8}=1 4m^{2}-13m+9=0\\\\D=(-13)^{2}-4*4*9=169-144=25=5^{2}\\\\m_{1}=\frac{13+5}{8}=\frac{9}{4}\\\\m_{2}=\frac{13-5}{8}=1](https://tex.z-dn.net/?f=4m%5E%7B2%7D-13m%2B9%3D0%5C%5C%5C%5CD%3D%28-13%29%5E%7B2%7D-4%2A4%2A9%3D169-144%3D25%3D5%5E%7B2%7D%5C%5C%5C%5Cm_%7B1%7D%3D%5Cfrac%7B13%2B5%7D%7B8%7D%3D%5Cfrac%7B9%7D%7B4%7D%5C%5C%5C%5Cm_%7B2%7D%3D%5Cfrac%7B13-5%7D%7B8%7D%3D1)
![(\frac{2}{3})^{x} =\frac{9}{4} \\\\(\frac{2}{3})^{x}=(\frac{2}{3})^{-2}\\\\x_{1}=-2\\\\(\frac{2}{3})^{x}=1\\\\(\frac{2}{3})^{x}=(\frac{2}{3})^{o}\\\\x_{2}=0 (\frac{2}{3})^{x} =\frac{9}{4} \\\\(\frac{2}{3})^{x}=(\frac{2}{3})^{-2}\\\\x_{1}=-2\\\\(\frac{2}{3})^{x}=1\\\\(\frac{2}{3})^{x}=(\frac{2}{3})^{o}\\\\x_{2}=0](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7Bx%7D%20%3D%5Cfrac%7B9%7D%7B4%7D%20%5C%5C%5C%5C%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7Bx%7D%3D%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7B-2%7D%5C%5C%5C%5Cx_%7B1%7D%3D-2%5C%5C%5C%5C%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7Bx%7D%3D1%5C%5C%5C%5C%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7Bx%7D%3D%28%5Cfrac%7B2%7D%7B3%7D%29%5E%7Bo%7D%5C%5C%5C%5Cx_%7B2%7D%3D0)
Ответ : - 2 , 0